2022
DOI: 10.35848/1347-4065/ac3a94
|View full text |Cite
|
Sign up to set email alerts
|

SiSn mediated formation of polycrystalline SiGeSn

Abstract: Si1-xSnx and Si1-x-yGexSny polycrystalline thin layers were grown using Sn nanodots as crystal nuclei. Si1-xSnx crystallization occurred around Sn nanodots, and the substitutional Sn content was estimated as high as 1.5%. In the case of the poly-Si1-x-yGexSny, Ge and Si were deposited simultaneously on the Sn nanodots, however, Ge was preferentially incorporated into the Sn nanodots, resulting in the formation of the poly-Si1-x-yGexSny with amorphous Si residue. It was found that the poly-Si1-xSnx formed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This study focused especially on reducing the thermal conductivity by the enhancement of phonon scattering. [8][9][10][11] Polycrystalline materials with a grain size larger than the mean free path of an electron and smaller than that of a phonon are effective in reducing the thermal conductivity. Therefore, poly-Si is expected to be a thermoelectric material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused especially on reducing the thermal conductivity by the enhancement of phonon scattering. [8][9][10][11] Polycrystalline materials with a grain size larger than the mean free path of an electron and smaller than that of a phonon are effective in reducing the thermal conductivity. Therefore, poly-Si is expected to be a thermoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Si and Ge can be crystallized at low temperatures around 150 °C by using Sn nanodots (Sn-ND) as a crystal nucleus. 10,11,21) On the other hand, even if the Sn-ND is used as crystalline nuclei, there is a possibility that amorphous Si may remain when the coverage of the Sn-ND is too low due to Sn agglomeration. Agglomeration of Sn substrate temperature dependence and the deposition ratio of Ge and Sn dependence of the Ge 1−x Sn x -ND are clarified in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the detailed electric properties of Ge 1−x−y Si x Sn y epitaxial layers have not yet been fully understood because most researchers mentioned above used semiconducting wafers for the growth substrate. We note that there are some reports on synthesizing single-crystalline 25) or polycrystalline [26][27][28] Ge 1−x−y Si x Sn y on insulating surfaces; however, an experimental investigation of the electrical properties of single-crystalline films have not been conducted. This paper presents both electrical and thermoelectric properties on n-type Ge 1−x−y Si x Sn y layers grown on semi-insulating GaAs wafers and discusses the Sn content effect on the properties.…”
Section: Introductionmentioning
confidence: 99%